2004
DOI: 10.1002/pssb.200304218
|View full text |Cite
|
Sign up to set email alerts
|

CBD‐Cd1−xZnxS thin films and their application in CdTe solar cells

Abstract: PACS 78.66.Hf, 81.05.Dz, 81.15.Lm, 84.60.Jt Composition, optical properties, structure properties, and surface morphology of thin films of Cd 1-x Zn x S (x ≤ 10%) prepared by chemical bath deposition (CBD) are reported. The best cell efficiency was 15.7%. It used a Cd 1-x Zn x S window layer, was confirmed by NREL (V oc = 840.1 mV, J sc = 24.81 mA/cm 2 , and FF = 75.55%), and had a CTO/ZTO/Cd 0.92 Zn 0.08 S/CdTe cell structure. The use of low zinc concentration in the Cd 1-x Zn x S layer and interdiffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…Various methods have been used to produce Cd 1 À x Zn x S films, including photochemical deposition [9], co-evaporation [10], chemical spray deposition [11] and chemical bath deposition [12]. Most methods, especially the solution deposition methods, require an annealing process in order to improve the film quality.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been used to produce Cd 1 À x Zn x S films, including photochemical deposition [9], co-evaporation [10], chemical spray deposition [11] and chemical bath deposition [12]. Most methods, especially the solution deposition methods, require an annealing process in order to improve the film quality.…”
Section: Introductionmentioning
confidence: 99%
“…The atomic percentage and weight percentage of Zn, Cd and S are given in table 2. Zhou et al [20] have determined the elemental ratio of ZnCdS thin film and it is observed that Zn ratio is much less than the Cd ratio.…”
Section: Surface Morphology and Energy Dispersive Spectroscopy (Eds) mentioning
confidence: 98%
“…Various thin-film deposition technique like vacuum evaporation, spray pyrolysis, dip technique, electrodeposition, chemical bath deposition (CBD), SILAR has been used to synthesize CdZnS thin films [7][8][9][10][11]. Among these deposition techniques, CBD is widely accepted as the preferable method to synthesize CdZnS thin film.…”
Section: Introductionmentioning
confidence: 99%